Extension Administrators’ Perspectives on Employee Competencies and Characteristics - Jeremy Elliott-Engel; Donna Westfall-Rudd; Megan Seibel; Eric Kaufman; Rama Radhakrishna ([TEST] Journal of Extension, 2021)
Extension administrators discussed the competencies and characteristics of Extension professionals as they explored how Extension will need adapt to changing clientele, both in who they are and how they want to receive information. Extension education curriculum is not fully preparing future Extension employees in all required competencies, falling short on use of technology, diversity and pluralism, volunteer development, marketing, and public relations, risk management, and the community development process. Additionally, the Extension educator workforce development pipeline is not preparing a demographically representative population, leaving state administrators struggling to hire prepared professionals, especially those with in-culture competency (e.g., racial and ethnic minority and urban).
Keywords: Extension professionals; competencies; diversity; Workforce development pipeline